2016
DOI: 10.1016/j.bbr.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, experience and inter-alpha inhibitor proteins on working memory and neuronal plasticity after neonatal hypoxia-ischemia

Abstract: Neonatal cerebral hypoxia-ischemia (HI) commonly results in cognitive and sensory impairments. Early behavioral experience has been suggested to improve cognitive and sensory outcomes in children and animal models with perinatal neuropathology. In parallel, we previously showed that treatment with immunomodulator Inter-alpha Inhibitor Proteins (IAIPs) improves cellular and behavioral outcomes in neonatal HI injured rats. The purpose of the current study was to evaluate the influences of early experience and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 106 publications
(117 reference statements)
7
54
1
Order By: Relevance
“…Thus, taken together with our in vitro findings, IAIPs expression in different brain regions and cell types in vivo suggest the potential for diverse functions in healthy brain and potentially in neonatal related brain disorders. Moreover, our recent finding that exogenous blood derived IAIPs have important neuroprotective effects (Threlkeld et al, 2014, Gaudet et al, 2016) would appear to suggest that endogenous IAIPs could also exert neuroprotective effects analogous to other previously reported neuroprotective factors such as FGF-2 (Nozaki et al, 1993, Noda et al, 2014). …”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Thus, taken together with our in vitro findings, IAIPs expression in different brain regions and cell types in vivo suggest the potential for diverse functions in healthy brain and potentially in neonatal related brain disorders. Moreover, our recent finding that exogenous blood derived IAIPs have important neuroprotective effects (Threlkeld et al, 2014, Gaudet et al, 2016) would appear to suggest that endogenous IAIPs could also exert neuroprotective effects analogous to other previously reported neuroprotective factors such as FGF-2 (Nozaki et al, 1993, Noda et al, 2014). …”
Section: Discussionsupporting
confidence: 63%
“…Exogenous IAIPs exhibit anti-inflammatory and neuroprotective effects in neonatal hypoxic-ischemic brain injury (Singh et al, 2010, Threlkeld et al, 2014, Gaudet et al, 2016). We have identified the wide spread existence of endogenous IAIPs in brain and other organs (Spasova et al, 2014), which has suggested the importance of examining the cellular expression and localization of IAIPs in brain as a first step to understand the physiological and molecular mechanisms of IAIPs in brain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations